The Relationship Between Market Environment Dimensions and Availability of Malaria Pills in Uganda - Pross Nagitta Oluka PhD; Marcia Mkansi PhD; George William Kajjumba PhD Candidate (SAGE Publishing, 2021)
Introduction This study sought to examine the contribution of relationship building (in terms of collaboration, information sharing and supply chain interdependence) on the availability of malaria treatment pills in public hospitals in Sub-Saharan Africa using data from Uganda. Methods By means of a cross-sectional survey research design, the study used a questionnaire strategy to collect quantitative data. Out of the 320 questionnaires that were distributed in 40 public hospitals, 283 were answered and returned, which yielded an 88% response rate. Structural equation modelling (SEM) was used to establish the relationship between measured variables and latent constructs. Results Drawing on the survey results, the confirmatory factor analysist and the Structural Equation Modelling clearly demonstrate that relationship building (in terms of collaboration, information sharing and supply chain interdependence) significantly influences the availability of Artemisinin-based combination therapies in public general hospitals in Uganda. Conclusion Policy-makers should focus on developing cheaper information technology tools to exchange information regarding stock levels, forecasting, quantification, orders, and dispensing. This study developed a measurement model for an inter-hospital relationship, using relational view theory, and it employs dimensions in terms of information sharing and supply chain interdependence to predict and explain the availability of malaria pills in government hospitals.